Study of Class 1, 2, and 3 Integrons, Antibiotic Resistance Patterns, and Biofilm Formation in Clinical Staphylococcus aureus Isolates from Hospital-Acquired Infections - Eman E. Hegazy; Wageih Salem ElNaghy; Marwa M. Shalaby; Sarah M. Shoeib; Nashwa S. M. Abdeen; Mohamed H. Fouda; Ola A. Elshora; Mohammed H. Elnaggar; Waleed Elrefaey; Rasha Youssef Hagag; Ahmed A. Elhadidy; Mohamed A. Elsebaey; et al. (Pathogens)
Antibiotic resistance and biofilm formation complicate Staphylococcus aureus infections, raising concerns for global health. Understanding antimicrobial resistance and biofilm formation in these pathogens is essential for effective infection management. The current research aimed to assess antibiotic resistance patterns, biofilm formation, and the occurrence of integron classes 1, 2, and 3 in clinical S. aureus isolates. The disc diffusion method tested antibiotic susceptibility. MRSA strains were identified by cefoxitin disc diffusion, and the mecA gene by PCR. The D-test also assessed macrolide–lincosamide–streptogramin B. A microtiter plate assay assessed biofilm formation. By PCR, integron classes were examined. Of the 63 S. aureus isolates, 25 were MSSA and 38 were MRSA. Pus (39.5%) was the most prevalent clinical source of MRSA isolates, while blood (24%) was the predominant source of MSSA isolates. MRSA isolates were more resistant to clindamycin, ciprofloxacin, ofloxacin, levofloxacin, tetracycline, and doxycycline than MSSA isolates. In total, 76.2% of the isolates produced biofilm. Biofilm-producing isolates were more resistant to cefoxitin and clindamycin. The isolates had 33.3% cMLSB resistance. The intI1 gene was found in 21 S. aureus isolates (33.3%), whereas the intI2 or intI3 genes were not detected. Our findings demonstrate the need for strict infection control to prevent the spread of resistant bacteria.